2021
DOI: 10.1111/jnp.12263
|View full text |Cite
|
Sign up to set email alerts
|

Measuring emotion recognition: Added value in diagnosing dementia of the Alzheimer’s disease type

Abstract: Neuropsychological tests, particularly for episodic memory, are used to classify patients in memory clinics. Still, the differential diagnosis between dementia of the Alzheimer’s disease type (Dementia‐AD), mild cognitive impairment (MCI), or major depressive disorder (MDD) is challenging. However, impairments in other domains, such as emotion recognition, an aspect of social cognition, might have additional value in distinguishing Dementia‐AD from MCI and MDD and hence signal progression of neurodegeneration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
2
10
0
Order By: Relevance
“…More specifically, for neurodegenerative disorders—Alzheimer’s disease [ 26 , 27 ] Parkinson [ 28 , 29 ] and Frontotemporal dementia [ 30 ], ER seems to function as an important criterion for the diagnosis and progression of the disease. Regarding AD, the findings agree that ER deficits play a particular role in the progression of dementia [ 5 , 31 , 32 ]. Key conclusions include impaired ability to recognize negative emotions, especially at the onset of the disease [ 33 ], while in the course of the disease the weaknesses seem to generalize to other emotions [ 26 , 34 ].…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…More specifically, for neurodegenerative disorders—Alzheimer’s disease [ 26 , 27 ] Parkinson [ 28 , 29 ] and Frontotemporal dementia [ 30 ], ER seems to function as an important criterion for the diagnosis and progression of the disease. Regarding AD, the findings agree that ER deficits play a particular role in the progression of dementia [ 5 , 31 , 32 ]. Key conclusions include impaired ability to recognize negative emotions, especially at the onset of the disease [ 33 ], while in the course of the disease the weaknesses seem to generalize to other emotions [ 26 , 34 ].…”
Section: Introductionsupporting
confidence: 65%
“…Regarding ER performance differences as a result of educational level, the interaction effect of education and diagnosis on the recognition of emotions has been found in some studies [ 5 ]. Sayaka Wada et al (2021) [ 85 ] found that the years of education are associated with volumes of the right orbital gyrus, the right inferior frontal gyrus, and the right supramarginal gyrus; the right supramarginal gyrus volume is also associated with the emotion recognition ability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it requires an administration time between 60 and 90 min that could interfere with the performance of the subject. Finally, the Ekman 60 Test assesses the emotional recognition of facial expressions, and is sensitive to deficits in dementia (Strijkert et al, 2021 ). Furthermore, this test showed accuracy in distinguishing between AD and bvFTD patients (Dodich et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Facial emotion recognition is an important basic social cognitive process, which in several studies was found to be impaired in patients with AD dementia. 5,6 Social behavioral changes are also prevalent in patients with AD dementia, and these changes can be experienced by close others as more burdening than cognitive symptoms: apathy is the most frequently reported symptom, but behaviors, such as agitation/aggression, disinhibition, and irritability, are also common and can be very disruptive. [7][8][9] However, whereas facial emotion recognition can be easily and objectively measured with neuropsychological tests, social behavioral changes are more difficult to assess: patients themselves are not always aware of behavioral changes, and close others may have difficulties providing a reliable impression of changed behaviors, despite increased burden.…”
mentioning
confidence: 99%